El medio oriente también es poesía: memorias en el Sheik a propósito del 50 aniversario de la muerte de Gibrán Jalil Gibrán - Calvo Oviedo, Marlen (2016)
This paper reviews an extraordinary hand-made edition of the El Sheik newspaper. In which we hope to close ties with the Arab world from a completely cultural focus, unallied to sociopolitical analysis to delve in to the poetry of one of the greatest Leban ese poets, Gibran Jalil Gibran. Our aim is to know his poetry and Lebanon by penetrating in to the poetic speech loaded with imagery and thoughts that transcend the local to become universal, allowing us to relocate Lebanese thought in to the realm of human productions that share meaningful links though poetic language as a communication bind.